Der grundrechtliche Schutz der digitalen Identität unter Berücksichtigung von Datenschutz- und IT-Sicherheitsrecht - Vettermann, Oliver (Schriften des Zentrums für Angewandte Rechtswissenschaft, Karlsruher Institut für Technologie, 2022)
The digital identity is the essential human data interface when interacting on the Internet or with IT systems to enable the multitude of services. No platform can be used without creating a (at least temporary) data construct to the retrieving user, which reflects the identity of the user and enables an assignment of the application data. This thesis examines the construct of digital identity and puts it into the fundamental rights framework. In doing so, data protection and IT security law are also consulted as concrete manifestations of fundamental rights.